Impacto das ecobarreiras na qualidade de água e redução da poluição flutuante em rio urbano (Ribeirão dos Carrapatos, Itaí, SP) - Moreira, Guilherme de Oliveira (Universidade Federal de São Carlos, 2021)
Solid waste, lack of basic sanitation and water pollution contribute negatively to the quality of life of cities and their inhabitants, in addition to the deficiency of public policies aimed at local sustainable development, as the vast majority of cities suffer without adequate infrastructure. The universalization of public services is distant considering that in the 21st century, 47% of the Brazilian population does not have basic sanitation and 16% does not have treated water. Eco-barriers are structures that aim to capture all types of floating waste improperly disposed of in water courses. In view of this, the general objective of the present study was to evaluate the impact that eco-barriers have on water quality and reduction of water pollution. The amount of floating solid waste collected in the periods from October 2019 to March 2020 was determined from the installed eco barriers, such as the water quality of the stretches evaluated with the presence of macrophytes (Eichhornia crassipes) and application of the Callisto Protocol to measure the degree of impact on the points assessed. It was observed through the protocol, that points 1 and 2 had the same score (20 points), which characterizes the stretches as impacts through mainly anthropic actions. In point 3, a slightly greater presence of vegetation was observed on the banks of the Ribeirão, in addition, there was no presence of oil in the water and no evident odor, classifying it as an “altered” section with 26 points. With regard to collected waste, 2018 was the year where the lowest monthly average of collection (294.9 kg) was obtained over a six-month period. The year of 2019 stood out, with just over a ton and in 2020, even considering the months of January, February and March of evaluation, the volume corresponded to 65.03% of the year of 2019. With regard to hydrological monitoring , there were statistically significant differences in the electrical conductivity parameters and total dissolved solids. Eco-barriers are functional structures because they prevent floating residues from reaching the Jurumirim dam and compromise the fauna, flora and all natural habitat. Regarding the use of Eichhornia crassipes, the values show that there is apparently an improvement in water quality, however other studies are essential with the increase in the sampling period and frequency
Impactos de las ecobarreiras en la calidad de água y reducción de la poluicion flotante en un rio urbano (Ribeirão dos Carrapatos, Itaí, SP)
Keywords: Recursos hídricos; Water; Ecobarreiras; Poluição hídrica; Macrófitas.; Ecobarriers; Water pollution; Macrophytes; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO